Mutation and Deletion of PAD1 and/or FDC1 and Absence of Phenolic Off-Flavor Production in Top- and Bottom-Fermenting Yeasts. (2nd January 2020) - Ogata, Tomoo; Yamada, Ryusuke; Ayuzawa, Ryo; Nakamura, Kensuke
Abstract: To convert ferulic acid into 4-vinylguaiacol (4-VG), Saccharomyces cerevisiae must have intact PAD1 and FDC1 genes. British-type top-fermenting yeast strains have nonsense mutations in both of these genes; whereas, bottom-fermenting yeast strains have a nonsense mutation in their S. cerevisiae -type FDC1, and have lost their S. eubayanus -type FDC1 and PAD1 genes. Here, top-fermenting yeast transformants in which wild-type PAD1 and FDC1 derived from the laboratory yeast S. cerevisiae S288C were inserted in the genome, exhibited ferulic acid decarboxylation activity. Similarly, bottom-fermenting yeast transformants expressing wild-type S. cerevisiae -type FDC1 or S. eubayanus -type FDC1 also exhibited ferulic acid decarboxylation activity. Thus, the lack of ferulic acid decarboxylation activity in bottom-fermenting yeast is due to mutation of the S. cerevisiae -type FDC1 gene, coupled with absence of the S. eubayanus -type FDC1 gene.